GENRES OF INTERNET COMMUNICATIONS: PRINCIPLES OF CLASSIFICATION - Іщук, С. М. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
The article deals with genres of Internet communications in connection with the development of the Internet language pragmatics.